La haie coupe, l’eau relie. Les continuités écologiques requalifiées par les agriculteurs - Sandrine Petit; Perrine Vandenbroucke (Développement Durable et Territoires)
The concept of “ecological network” comes from landscape ecology. It refers to reservoirs of biodiversity connected through corridors. The “Trame verte et bleue” (greenway) is an application of this ecological continuity concept in the French public policies. The “Trame verte et bleue” conveys different representations than those of the farmers. For them, more than corridors, hedges are viewed as barriers to the wind, prevent people and animals from moving, and require trees to be pruned. But hedges, as natural resources, are also come under intimate experience, and involve past generations and actors of the territory. Even though management approaches of farmers, city-dwellers and nature managers converge in mapping and categorizing natural resources, we advocate for a relational approach. This approach allows to recognize the diversity of forms those resources are qualified and managed.